GLI2-HRD1 axis facilitates 5-FU resistance in gastric cancer cells by regulating ubiquitination degradation of UCK2 - Chaorong Xue; Xuanzi Zhang; Wanling Yu; Hanbin Lin; Junrong Zhang; Jiawen Liu; Zongqi Weng; Manduo Ouyang; Xinjian Lin (Translational Oncology)
5-Fluorouracil (5-FU) is a primary chemotherapeutic agent for treating gastric cancer (GC), yet resistance to 5-FU frequently limits its effectiveness and contributes to poor patient outcomes. This study investigated the molecular mechanisms by which uridine-cytidine kinase 2 (UCK2) influences 5-FU resistance in GC. Using a genome-wide CRISPR knockout (GeCKO v2) library, we identified UCK2 as a critical gene for 5-FU sensitivity in GC cells. In 5-FU-resistant GC cells, the transcription factor GLI2 and the E3 ubiquitin ligase HRD1 were both upregulated, while UCK2 expression was significantly reduced. Functional assays demonstrated that lowering UCK2 or increasing HRD1 expression enhanced GC cell proliferation and 5-FU resistance, with HRD1 mediating 5-FU resistance through the ubiquitination and degradation of UCK2. Furthermore, GLI2 overexpression promoted cell proliferation and resistance to 5-FU by transcriptionally activating HRD1. In vivo experiments confirmed that GLI2 knockdown effectively reduced tumor growth under 5-FU treatment, an effect that was reversed by HRD1 overexpression. These findings reveal the GLI2-HRD1-UCK2 axis as a crucial pathway for modulating 5-FU resistance in GC, suggesting new potential targets for overcoming chemoresistance in GC therapy.